Composição microbiológica cultivável do granizo de uma tempestade no sudoeste do Paraná - Tsay, Gabriela Salles (2017)
The hailfall is a recurrent phenomenon in storms that reach Brazil´s South Region. Nevertheless, little scientific investigation has been conducted in order to understand the main characteristics and involved mechanisms. Physical, chemical and microbiological characterization of hailstones consists on an important stage to understand processes associated to events that culminate in hail. Thus, this work aims to present, for the first time, a characterization of microbiological composition of hail from a hailstorm occurred in southwestern of Paraná state. Hailstones from a storm occurred in July 2016 were physically characterized (mass, diameter, volume, density), and submitted to a decontamination protocol established in this work. Melt hailstone water was plated to grow in MHA medium for bacteria isolation. We counted and characterized CFU, resulting in 76 representative isolates that were submitted to morphotintorial analysis by Gram stain technique. UPGMA software delivered a phenotypic grouping that enabled the selection of 22 representative isolates to be forwarded to the genetic sequencing service. We extracted total DNA from these isolates by commercial extraction kit and performed a PCR for amplification of ribosomal RNA (rRNA) 16S region. A specialized company provided the genetic sequences to the generated amplicon. The genetic sequences were submitted to BLAST for similarity search in GenBank. As a result, we identified 8 genera and 11 species of environmental bacteria, which were predominantly rod-shaped, Gram-positive, and spore-forming. Bacillus and Paenibacillus represented 50% of the species identified and they were mentioned in other studies as potential ice nucleators. Sporosarcina was the only genus that could not be found in our literature searches regarding air, cloud water or hail samples. Regarding the physical properties, hailstones had average diameters between 1.15 and 1.75cm, and mean densities ranging from 0.8 to 1.0g / mL, consistent with the literature. Finally, we present suggestions for future studies in the conclusion.